The finance of the war - Thompson, Newman (Statistical and Social Inquiry Society of Ireland, 1919)
This paper naturally divides itself into three sections:? (1) The financial steps taken at the outbreak of war; (2) The methods by which the expenditure of the war have been met; and (3) Some observations upon the facts set forth in the preceding sections.
Read February 22nd, 1918
Keywords: War expenditure; National debt; War loan; 314.15